2022
DOI: 10.3390/f13050798
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Economic Viability of Forest Certification: A Systematic Review

Abstract: In the face of accelerating forest degradation and deforestation, forest certification emerged in the early 1990s as a voluntary and market-based mechanism to promote environmentally appropriate, socially beneficial, and economically viable management of the world’s forests. A key goal of forest certification is to reduce forest degradation and deforestation while enhancing forest enterprises’ economic viability. However, whether forest certification contributes to meeting such goals is unclear. We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 125 publications
1
2
0
Order By: Relevance
“…In addition, they are not likely to have training in various topics of culture and education, social integration is less than in certified ejidos, and workers do not have safety equipment in any of their areas. This study supports the need to have data on the impacts of forest certification of cases of a specific territory in order to be compared with regional scales as recommended by Wolff and Schweinle (2022).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, they are not likely to have training in various topics of culture and education, social integration is less than in certified ejidos, and workers do not have safety equipment in any of their areas. This study supports the need to have data on the impacts of forest certification of cases of a specific territory in order to be compared with regional scales as recommended by Wolff and Schweinle (2022).…”
Section: Discussionsupporting
confidence: 83%
“…However, despite variations in forest coverage across countries, statistics showed that between 2000 and 2018, the quality of more than 60% of the forest in Europe has increased [3]. Forest certification has made significant progress in Europe in promoting sustainable forest management practices [21], a concept that has been growing in acceptance and popularity in both national forest plans and international forest policy [40]. Our results demonstrated that the pattern observed within European countries in relation to forest coverage is not yet fully reflected in the proportion of certified forest.…”
Section: Discussionmentioning
confidence: 99%
“…Forest certification was established as a tool to promote sustainable forest management practices and to reduce the negative impacts of exploiting forests and their ecosystems [6,21]. The sustainable forest management framework should contribute to the global balance of ecological, economic, and social needs by making sure that forest resources are managed in a way that satisfies current demands without endangering the needs of future generations [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding why profit-seeking firms engage in sustainable behavior has been an important focus of sustainability literature [13,14], yet there is no consensus around whether sustainability improves a firm's financial performance [15,16]. However, evidence suggests positive relationships between sustainability and financial performance, with a number of mediators [17,18].…”
Section: Sustainability In Family Firmsmentioning
confidence: 99%